Bio-processing Plantation by-products with White Oyster Mushroom (Pleurotus ostreatus) to Improve Fermentability and Digestibility Based on Substrate Type and Fermentation Time - Yulia Riska Azzahra; Toto Toharmat; Iwan Prihantoro (Faculty of Animal Science, Universitas Gadjah Mada, 2022)
Plantation by-products can be used as livestock feed with proper processing, optimizing the feed efficiency of palm kernel cake (PKC), empty oil palm bunch (EOPB), and acacia sawdust (AS). This study aimed to improve the usability of the byproducts as alternative feed through the Pleurotus ostreatus fermentation process. To this end, a 3×3 factorial, completely randomized design was applied. Factor A was the type of substrate, P1 = PKC, P2 = EOFB and P3 = AS. Factor B was the fermentation period, T1 = 0 d, T2 = 30 d and T3 = 60 d. The collected data were analyzed using analysis of variance (ANOVA), and the significantly different result was further tested using Duncan Test. The observed variables include Neutral Detergent Fiber (NDF), acid detergent fiber (ADF), hemicellulose, pH value, dry matter digestibility (DMD), organic matter digestibility (OMD), N-NH 3 , and volatile fatty acids (VFA). The study result showed that P.ostreatus mushroom in various substrate types did not significantly affect the fiber fraction of NDF, ADF, and Hemicellulose. This study also found that the interaction of substrate type and fermentation duration significantly affects dry matter digestibility, organic matter digestibility, N-NH 3 production, and VFA values. This study concluded P. ostreotus increased the nutritional value and digestibility of the by- product from plantation processing. The best fermentation duration was 60 d PKC was found to have the highest digestibility value, and the best interaction was found in PKC with 60 d of fermentation.